Measurement model of critical success factors for energy management in Malaysia university / Alia Abdullah Saleh - Alia, Abdullah Saleh; Siti Norsazlina, Haron; Nur Azfahani, Ahmad; Nor Eeda, Ali (Universiti Teknologi MARA, Perak, 2018)
The increasing number of staff and students in Malaysian universities has led to consume energy excessively. The activities of the university's management to reduce the energy expenditure is critical, where critical success factors (CSFs) are the few issues that must be addressed as well as to ensure the accomplishment of an organisation. Unfortunately, most Malaysian universities are lagging in determining the relationship of identifying CSFs for EM with KPIs towards a sustainable university. Therefore, this research focuses on critical success factors (CSFs) for energy management (EM) towards Malaysian sustainable university. This inquiry is broadened by taking a conceptual measurement model using Partial Least Square-Structural Equation Modeling (PLS-SEM). The assessment demonstrates that the construct of CSFs for EM which comprises of ‘Top Management Provision’, ‘Commitment from EM Team’, ‘Planned Maintenance Management’, ‘Consciousness’ and ‘Good Relationship among stakeholders’ were maintained and some of the indicators relate to this construct were expelled. In conclusion, the findings obtained can assist the decision maker in the university to identify the areas that need improvement in order to increase the performance of EM. This study is very beneficial to all universities, especially universities in Malaysia which practice EM. The existing guidelines also can be improved so as to be more effective and able to be applied to all universities in Malaysia.